2014
DOI: 10.2298/sarh1408431z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dsDNA, anti-nucleosome and anti-C1q antibodies as disease activity markers in patients with systemic lupus erythematosus

Abstract: Anti-nucleosome and anti-C1q antibodies demonstrated association with SLE and lupus nephritis activity, suggesting their potential usefulness in making predictions about lupus nephritis and assessment of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
3
22
1
3
Order By: Relevance
“…Regarding the relationship between double positive antibodies and laboratory findings, our study showed that patients with double positive antibodies have a significantly higher disease activity as assessed by ECLAM score, elevated ESR, lower serum albumin and low C3 levels. Our findings parallel those of other authors [38,39].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the relationship between double positive antibodies and laboratory findings, our study showed that patients with double positive antibodies have a significantly higher disease activity as assessed by ECLAM score, elevated ESR, lower serum albumin and low C3 levels. Our findings parallel those of other authors [38,39].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to C1q complement, serum levels of complements C3 and C4 are also decreased in SLE patients [ 24 ]. Therefore, levels of C1q, C3, and C4 and/or the autoantibodies to C1q, dsDNA, and chromatin/nucleosome in serum are important immunological markers in the diagnosis of SLE, particularly for LN disease [ 7 , 10 , 12 , 13 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A strong association between αC1q ab and active renal disease has been demonstrated [18]. Only nine studies have longitudinal data permitting this specific assessment (including 10,14), although other reports have supported its potential for this use [9,10,12,17]. The present study measured the levels of αC1q ab in a cohort of diagnosed and treated Western Australian SLE patients using a commercial ELISA kit.…”
Section: Introductionmentioning
confidence: 83%
“…In the last decade, the relationship between αC1q ab and clinical profiles in SLE patients, as well as relationships with other laboratory parameters has been investigated. It has been reported by several groups [6,[8][9][10] that the levels of αC1q ab titers are usually significantly higher in SLE patients than healthy controls or non-SLE autoimmune patients. The concentrations of αC1q ab correlate with disease activity and/or severity [6,[8][9][10][11][12][13][14][15][16][17][18][19] as well as with other laboratory parameters including complement protein C3 and/or C4 concentrations, dsDNA ab, proteinuria and the presence of immune complexes [6,8,11,12,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 97%